Association of OCT4, SOX2, and NANOG expression with oral squamous cell carcinoma progression. (25th July 2015) - Fu, Ting‐Ying; Hsieh, I‐Chien; Cheng, Jiin‐Tsuey; Tsai, Meng‐Han; Hou, Yu‐Yi; Lee, Jang‐Hwa; Liou, Huei‐Han; Huang, Sheng‐Feng; Chen, Hung‐Chih; Yen, Leing‐Ming; Tseng, Hui‐Hwa; Ger, Luo‐Ping
Abstract : Background: OCT4, SOX2, and NANOG are major transcription factors related to stem cell self‐renewal and differentiation. The aim of this study was to examine the association of OCT4, SOX2, and NANOG expression levels with the development and prognosis of patients with oral squamous cell carcinoma (OSCC). Materials and Methods: Expression levels of OCT4, SOX2, and NANOG were evaluated by immunohistochemistry with tissue microarray slides of 436 OSCC, 362 corresponding tumor‐adjacent normal (CTAN) tissues, and 71 normal uvula epithelium tissues. The clinicopathologic and follow‐up data of the OSCC patients were recorded. Results: OCT4 expression was significantly higher in normal and CTAN tissues than in tumor tissue (both P < 0.001). SOX2 expression in CTAN tissue was significantly higher than that in normal ( P = 0.021) and tumor tissues ( P < 0.001). However, NANOG expression was significantly higher in CTAN ( P = 0.014) and tumor tissues ( P = 0.009) than in normal tissue. Higher OCT4 and SOX2 expressions were associated with earlier AJCC stage ( P = 0.002 and P < 0.001), small tumor size ( P = 0.017 and P = 0.001), and the absence of lymph node metastasis ( P = 0.015 and P = 0.025). Higher levels of SOX2 expression were associated with better disease‐specific survival ( P = 0.002) even after adjustment for clinicopathologic factors. Discussion: OCT4 and SOX2 are biomarkers of tumorigenesis and early stage OSCC. SOX2 is an independent prognostic factor for OSCC.